Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0194599818794456
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Posttracheostomy Tracheal Stenosis

Abstract: Objective To determine the incidence of posttracheostomy tracheal stenosis and to investigate variables related to the patient, hospitalization, or operation that may affect stenosis rates. Study Design A combined retrospective cohort and case-control study. Setting Tertiary care academic medical center. Subjects and Methods A total of 1656 patients who underwent tracheostomy at a tertiary care medical center from January 2011 to November 2016 were reviewed for evidence of subsequent tracheal stenosis on airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
90
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 21 publications
3
90
0
3
Order By: Relevance
“…18,[22][23][24] Rates have been reported to vary between 1.5% and 1.7% depending on various factors, such as obesity, the need for a wide diameter tracheostomy and long-term mechanical ventilation. 25 In a series of 88 percutaneous tracheostomy cases, Wagner et al reported the development of TS in eight (9.1%) patients. 24 The results of the current study were consistent with the literature in respect to TS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[22][23][24] Rates have been reported to vary between 1.5% and 1.7% depending on various factors, such as obesity, the need for a wide diameter tracheostomy and long-term mechanical ventilation. 25 In a series of 88 percutaneous tracheostomy cases, Wagner et al reported the development of TS in eight (9.1%) patients. 24 The results of the current study were consistent with the literature in respect to TS.…”
Section: Discussionmentioning
confidence: 99%
“…TS is the narrowing of the tracheal lumen by fibrosis or granulation tissue . Rates have been reported to vary between 1.5% and 1.7% depending on various factors, such as obesity, the need for a wide diameter tracheostomy and long‐term mechanical ventilation . In a series of 88 percutaneous tracheostomy cases, Wagner et al .…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic subglottic stenosis, which can extend into the upper trachea, plays a role. However, data suggests that the risk associated with intubation is the most common cause of tracheal stenosis, and intubation risk may excessively affect women . Another consideration is that women in this sample may be more symptomatic or relatively healthier than men with tracheal stenosis and therefore were more likely to undergo tracheoplasty.…”
Section: Discussionmentioning
confidence: 94%
“…There is good evidence that the risk of tracheal stenosis after tracheostomy is increased among obese patients . The etiology may be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation